Errors and Complications during and After Endodontic Treatment - K. F, Turayeva; oʻgʻli, Nasipkulov Javoxir Sirojjon; oʻgʻli, Urazov Bayramali Mamadali (American Journal of Bioscience and Clinical Integrity, 2025)
Errors, even unintentional ones, interfere with the impartial and objective clinical judgment of the dentist. On the other hand, the choice of adequate approaches to resolve certain clinical situations depends on the errors made in the past and how well the doctor was able to understand the reasons for their occurrence. If we analyze the last patient who came to you with the problem of unsuccessful endodontic treatment and successfully installed a dental implant, the idea would arise that implantation is a more predictable intervention than endodontics. And this would also be a mistake. Current trends in endodontics include the use of a microscope to perform iatrogenic interventions.